Turnover of multiple sex chromosomes in Harttia catfish (Siluriformes, Loricariidae): a glimpse from whole chromosome painting - Sassi, Francisco de Menezes Cavalcante; Deon, Geize Aparecida; Sember, Alexandr; Liehr, Thomas; Oyakawa, Osvaldo Takeshi; Moreira Filho, Orlando; Bertollo, Luiz Antonio Carlos; Vicari, Marcelo Ricardo; Cioffi, Marcelo de Bello (Frontiers in Genetics, 2023)
The remarkable fish biodiversity encompasses also great sex chromosome variability. Harttia catfish belong to Neotropical models for karyotype and sex chromosome research. Some species possess one of the three male-heterogametic sex chromosome systems, tThe standard XY, and multiple X1X2Y orand XY1Y2, while other members of the genus sex chromosome systems are present in different species of the genus, nested along with representatives withhave yet uncharacterized modes of sex determination. Particularly the XY1Y2 multiple sex chromosome system hashows a relatively low incidence among vertebrates, and it has not been yet poorly investigatedthoroughly investigated. Previous research suggested two independent X-autosome fusions in Harttia which led to the emergence of XY1Y2 sex chromosome system in three of its species. In this study, we investigated evolutionary trajectories of synteny blocks involved in this XY1Y2 system by probing six Harttia species with whole chromosome painting (WCP) probes derived from the X (HCA-X) and the chromosome 9 (HCA-9) of H. carvalhoi. We found that both painting probes hybridize to two distinct chromosome pairs in Amazonian species, whereas the HCA-9 probe paints three chromosome pairs in H. guianensis, endemic to French GuianaGuyanese drainages. These findings demonstrateing distinct evolutionary fates of mapped synteny blocks and thereby elevated karyotype dynamics in Harttia among the three evolutionary clades.